2021
DOI: 10.3389/fimmu.2021.659444
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a CD8+ T Cell Infiltration-Related Signature for Melanoma Patients

Abstract: AimImmunotherapy shows efficacy in only a subset of melanoma patients. Here, we intended to construct a risk score model to predict melanoma patients’ sensitivity to immunotherapy.MethodsIntegration analyses were performed on melanoma patients from high-dimensional public datasets. The CD8+ T cell infiltration related genes (TIRGs) were selected via TIMER and CIBERSORT algorithm. LASSO Cox regression was performed to screen for the crucial TIRGs. Single sample gene set enrichment analysis (ssGSEA) and ESTIMATE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 78 publications
0
29
0
Order By: Relevance
“…Previous studies suggested that NK cell-related signature, CD8 + T cell-related signature, PD-L1 expression, or TMB could be used to predict the prognosis of CM patients (14,32,33). The cTICscore, compared with these predictors, seemed to have better predictability based on the AUC of the time-dependent ROC curves (Figure 1C).…”
Section: Core Tumor−infiltrating Immune Cell Score (Cticscore) Identi...mentioning
confidence: 83%
See 2 more Smart Citations
“…Previous studies suggested that NK cell-related signature, CD8 + T cell-related signature, PD-L1 expression, or TMB could be used to predict the prognosis of CM patients (14,32,33). The cTICscore, compared with these predictors, seemed to have better predictability based on the AUC of the time-dependent ROC curves (Figure 1C).…”
Section: Core Tumor−infiltrating Immune Cell Score (Cticscore) Identi...mentioning
confidence: 83%
“…CM patients stratified into two subgroups using the median cTICscore as the cutoff value showed distinct prognosis in all the three datasets and the external validating GSE54467 ( Figure 1B ). Previous studies suggested that NK cell–related signature, CD8 + T cell-related signature, PD-L1 expression, or TMB could be used to predict the prognosis of CM patients ( 14 , 32 , 33 ). The cTICscore, compared with these predictors, seemed to have better predictability based on the AUC of the time-dependent ROC curves ( Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guanylate-binding protein 4(GBP4) belongs to the interferon-stimulated factor that acts as a protective factor in host defense, and several genes from the GBP family act as tumor suppressors [ 27 , 28 ]. In addition, a recent study found the GBP4 was positively correlated with immune cell infiltration in melanoma patients [ 29 ]. Docking protein-1 (DOK1), a tumor suppressor, is frequently downregulated in human tumors such as ovarian cancer, Burkitt lymphoma, head and neck cancer (HNC), chronic lymphocytic leukemia (CLL), lung cancer, and breast cancer [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…C2.cp.k egg.v7.1.symbols.gmt was chosen as the gene set database. Signaling pathways that meet the following criteria can be significantly enriched: nominal p-value < 0.05, q-value < 0.25, and normalized enrichment score > 1 [ 27 ].…”
Section: Methodsmentioning
confidence: 99%